Efficacy of Nitric Oxide Administration in Attenuating Ischemia/Reperfusion Injury During Neonatal Cardiopulmonary Bypass. Issue 4 (July 2020) - Elzein, Chawki; Urbas, Cynthia; Hughes, Bonnie; Li, Yi; Lefaiver, Cheryl; Ilbawi, Michel; Vricella, Luca
Objective: Nitric oxide (NO) plays several protective roles in ischemia/reperfusion (I/R) injury. Neonates undergoing the Norwood procedure are subject to develop I/R injury due to the immaturity of their organs and the potential need to interrupt or decrease systemic flow during surgery. We hypothesized that NO administration during cardiopulmonary bypass (CPB) ameliorates the I/R and could help the postoperative recovery after the Norwood procedure. Methods: Twenty-four neonates who underwent a Norwood procedure were enrolled in a prospective randomized blinded controlled trial to receive NO (12 patients) or placebo (12 patients) into the oxygenator of the CPB circuit during the Norwood procedure. Markers of I/R injury were collected at baseline (T0), after weaning from CPB before modified ultrafiltration (T1), after modified ultrafiltration (T2), and at 12 hours (T3) and 24 hours (T4) after surgery, and they were compared between both groups, as well as other postoperative clinical variables. Results: There was no difference in age, weight, anatomical diagnosis, CPB, and aortic cross-clamp time between both groups. Troponin levels were lower in the study group at T1 (0.62 ± 58 ng/mL vs 0.87 ± 0.58 ng/mL, P = .31) and became significantly lower at T2 (0.36 ± 0.32 ng/mL vs 0.97 ± 0.48 ng/mL, P = .009).There were no significant differences between both groups for all other markers. Despite a lower troponin level, there was no difference in inotropic scores or ventricular function between both groups. Time to start diuresis, time to sternal closure and extubation, and intensive care unit and hospital stay were not different between both groups. Conclusion: Systemic administration of NO during the Norwood procedure has myocardial protective effects (lower Troponin levels) but we observed no effect on postoperative recovery. Larger sample size may be needed to show clinical differences.